Mechanical optimization of bipedal gait movement - Espiritu, Joshua Romeo S. (Quezon City College of Enginnering, University of the Philippines Diliman, 2013)
Analysis of Bipedal Gait of the knee and hip joints in human show a fluctuating intensity of Torque and Speed. When replicating this feat artificially, electric motors are used to move the limbs of the machine. The motor has to be able to provide the maximum output required by the limb to meet the full requirements of the movement and the larger the Torque, the larger the motor needed. However, the maximum Torque is only used for a small interval compared to the complete gait. The goal of this research is to be able to provide a mechanism that will allow a more efficient use of a smaller motor to power the movement. The theory used is similar to how different sizes of gears can change the output speed and torque of its input motor. However, this paper will use Four-Bar Linkage over Gears to reduce the torque and the variability in torque requirements. The research was able to both significantly reduce the motor torque requirements, as well as maximize the usage of the motor capacity by reducing the variations in torque requirements.
Thesis (M.S. Mechanical Engineering)--University of the Philippines, Diliman.
Keywords: Bipedalism